High‐resolution melting assay for genotyping of IFNL4‐associated dinucleotide variant rs368234815. (15th May 2014) - Galmozzi, E.; Facchetti, F.; Perbellini, R.; Aghemo, A.; Antonelli, G.
Abstract Interferon‐λ4‐related dinucleotide variant rs368234815 TT/‐G is strongly linked with rs12979860 polymorphism, the most important genetic marker connected to treatment‐induced hepatitis C virus clearance. Due to additional baseline information that rs368234815 polymorphism could provide for the management of chronic hepatitis C, we developed and validated a high‐resolution melting genotyping assay using 193 patients with chronic hepatitis C.